Kesehatan Mental Dalam Keluarga : Studi Literatur Peranan Dukungan Keluarga Dalam Meningkatkan Kesehatan Mental Remaja - Hema Dayita (Institute of Advanced Knowledge and Science, 2026)
This study aims to improve understanding of the relationship between family support and mental health, focusing on the crucial role of family in adolescent development. Adolescence is a significant transition phase from childhood to adulthood, marked by fundamental changes in the biological, intellectual, psychosocial and economic aspects of individuals. This study adopts a literature review method, which involves searching and reviewing various journals, research articles, and other relevant references to test and develop existing concepts or theories. This approach specifically emphasizes the collection of analysis and assessment of data from various sources.